The impact of the COVID-19 pandemic on maternal healthcare utilization in Ngawi regency, Indonesia: an interrupted time-series analysis - Eny Qurniyawati; Levi Nadila Putri; Dinda Ardanila; Ririh; Yasmin Nuriyah Rahmadani; Erni Astutik; Hiba Adam; Linda Andriani (Universitas Gadjah Mada, 2026)
Purpose: The burden of COVID-19 threatened the health system and reversed gains in healthcare services. It led to significant disruptions in access and delivery of maternal healthcare. In consequence, the Maternal Mortality Rate (MMR) in Ngawi Regency is 276.9 per 100,000 live births, surpassing the MMR for East Java, and the coverage of maternal health indicators has declined during the pandemic. This study aims to investigate the effect of the COVID-19 pandemic on maternal healthcare in Ngawi Regency, Indonesia. Methods: An Interrupted Time-Series (ITS) design was used to assess the impact of the COVID-19 outbreak on the outcome variable, the number of women who utilized maternal healthcare services. Data were collected from January 1st, 2019, to December 31st, 2021. An interrupted-time series analysis was conducted using an Autoregressive Integrated Moving Average (ARIMA) model. Results: A significant decline of 54 women (95% CI -80.45 to -27.06) in fourth maternal healthcare utilization at pandemic onset. The following reductions were also observed in health-facility delivery and postnatal care utilization: 66 women (95% CI: -112.04 to -20.51) and 106 women (95% CI: -184.60 to -26.49); however, no significant changes in first antenatal care or obstetric-complication treatment at pandemic onset. The statistically significant reductions in fourth antenatal care, health-facility delivery, and postnatal care utilization were 3 (95% CI: -5.14 to -1.67), 7 (95% CI: -11.66 to -1.85), and 11 (95% CI: -15.50 to -5.51) women, respectively. Conclusion: The COVID-19 pandemic has disrupted the fourth antenatal care, health facility delivery, and postpartum care in Ngawi Regency. The disruption due to mobility restrictions, a shift in focus and health resources towards combating COVID-19, and a decrease in the frequency of antenatal care visits.